2014
DOI: 10.7763/ijtef.2014.v5.423
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Service Innovation on Perceived Value and Guest’s Return Intention — A Study of Luxury Hotels in Ho Chi Minh City, Vietnam

Abstract: Abstract-This research aimed to explore factors affecting to service innovation and how well the influence of innovative practices on the way guests perceiving value and their intention to return the hotels. Quantitative research approach was applied with convenient sampling technique and a completed set of well-structured questionnaires was delivered directly to 300 respondents who were foreign tourists staying at three to five-star hotels in Ho Chi Minh City, Vietnam. This study found that marketing-focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Service innovation Khuong and Giang (2014) explained that innovation is one of the most competitive advantages that make a company stands up to the fierce competition. Also, service innovation is perceived as the concept of service, a means of customer interaction, a system to provide services, or the concept of technology that is new or variable to a great extent.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Service innovation Khuong and Giang (2014) explained that innovation is one of the most competitive advantages that make a company stands up to the fierce competition. Also, service innovation is perceived as the concept of service, a means of customer interaction, a system to provide services, or the concept of technology that is new or variable to a great extent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, Verma et al (2008, p.7) defined service innovation as "The introduction of new or novel ideas which focus on services that provide new ways of delivering a benefit, new service concepts, or new service business models through continuous operational improvement, technology, investment in employee performance, or management of the customer experience". Furthermore, the services industry covers a large scale of activities, and many studies support the types that affect innovation services, namely innovative hotel types, customization of service, use of information technology, process innovation, marketing-focused innovation, brand differentiation, and pricing innovation (Khuong & Giang, 2014). Veerakumaran (2009) pointed out that innovation in the service is intended to provide new services as well as the development of the available services.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that the further research should invest more time and select more factors to build more effective research model. The accuracy and effectiveness should be better when additional factors are investigated such as: Price Perception [40], Marketing focused innovation [3], Word of Mouth [41]. Future study can consider implementing these factors into the research models to investigate.…”
Section: B Limitations and Implications For Future Researchmentioning
confidence: 99%
“…Additionally, hotel companies are facing with increasing competition from other lodging properties such as extended-stay properties, bed-and-breakfasts and campgrounds [2]. Therefore, building the sustainable competitive advantage for hotels has become an important consideration [3]. The sustainable and retain the customers for the future.…”
Section: Introductionmentioning
confidence: 99%